Frequency-domain analysis of performance of a wind turbine - Hernández Perdomo, W. (2015)
The frequency-domain analysis of the performance of a wind turbine that is placed in a mountainous complex terrain is presented. The variables of interest were the wind speed and the active power of the wind turbine, and the experimental data for the analysis were collected for three months with a sampling time of 10 minutes. The power spectral density (PSD) of the wind speed and of the active power of the wind turbine were obtained for every day of the three months under analysis, and this information was used to estimate the magnitude squared of the frequency response of the system and to estimate the average value of the magnitude squared of the frequency response. Then, the energy distribution of the wind turbine over a range of frequencies was analysed.